The Role of the Community in Environmental Monitoring : A Legal Perspective - Ramlani Lina Sinaulan; Marsha Angelina Utoyo Sinaulan; Mohamad Ismed (International Forum of Researchers and Lecturers, 2025)
Community participation in environmental monitoring is an essential component of the environmental legal system in Indonesia. This article aims to examine the strategic role of the community in the national legal framework, particularly under Law No. 32/2009 on Environmental Protection and Management. Using normative juridical methods and descriptive analysis, this article discusses the rights and obligations of the community, forms of participation, and challenges faced in the implementation of environmental supervision. The results of the study show that although the space for participation has been opened legally, in practice, it still faces obstacles such as limited access to information, lack of legal protection, and lack of community capacity. Therefore, strengthening legal literacy, information transparency, and protection of whistleblowers are important steps to encourage the active role of the community. This article recommends a collaborative approach between the state and the community to realise fair, participatory and sustainable environmental governance